Implementation of Broadcast Code of Conduct and Broadcast Program Standards at Celebes TV Makassar - Aningsih, Gusti; Sultan, Moehammad Iqbal; Sonni, Alem Febri (State Islamic Institute of Bone, Indonesia, 2024)
This paper discusses the Implementation of Broadcasting Code of Conduct and Broadcast Program Standards at Celebes TV Makassar. this research, the author uses Qualitative research (field research). Data collection is done by interview, observation and documentation. The results showed that The implementation of Broadcasting Code of Conduct and Broadcast Program Standard on Celebes TV Makassar broadcast program is by following the regulation set by Indonesian Broadcasting Commission (KPI) about Broadcasting Code of Conduct and Broadcast Program Standard (P3SPS) 2012. In disseminating information, it must be in accordance with the existing facts and before the information is disseminated to the audience or public, it is necessary to research the truth of the information so that there is no misunderstanding between the information giver and the information receiver.